2015
DOI: 10.1177/1098612x15590867
|View full text |Cite
|
Sign up to set email alerts
|

Stress in owned cats: behavioural changes and welfare implications

Abstract: Domestic cats are exposed to a variety of stressful stimuli, which may have a negative effect on the cats' welfare and trigger a number of behavioural changes. Some of the stressors most commonly encountered by cats include changes in environment, inter-cat conflict, a poor human-cat relationship and the cat's inability to perform highly motivated behaviour patterns. Stress is very likely to reduce feed intake, and stress-related anorexia may contribute to the development of potentially serious medical conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
136
0
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(165 citation statements)
references
References 118 publications
(154 reference statements)
0
136
0
9
Order By: Relevance
“…The ability to accurately predict and understand individual differences in stress sensitivity and response may allow us to understand responses to pain and suboptimal welfare conditions (Ijichi et al, 2013b;Koolhaas et al, 2010). If used in cat rehoming centres, the FTP may indicate which cats could need intervention such as environmental enrichment or the use of pheromones (Amat, Camps and Manteca, 2015) to reduce their stress levels (Vainionpää et al, 2013). Improved welfare can also have an indirect benefit in rescue facilities by increasing the chances of adoption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to accurately predict and understand individual differences in stress sensitivity and response may allow us to understand responses to pain and suboptimal welfare conditions (Ijichi et al, 2013b;Koolhaas et al, 2010). If used in cat rehoming centres, the FTP may indicate which cats could need intervention such as environmental enrichment or the use of pheromones (Amat, Camps and Manteca, 2015) to reduce their stress levels (Vainionpää et al, 2013). Improved welfare can also have an indirect benefit in rescue facilities by increasing the chances of adoption.…”
Section: Discussionmentioning
confidence: 99%
“…This environment may cause stress, especially for feral or older individuals who may be less flexible in response to this environmental change. Stress is associated with avoidance and aggressive behaviour (Amat, Camps and Manteca, 2015;Siegford et al, 2003) which are considered undesirable to potential new owners. This may impact on adoption rates if this behaviour is not resolved.…”
Section: Introductionmentioning
confidence: 99%
“…When veterinarians examine a cat with a self-directed behaviour, all possible underlying causes should always be considered. In fact, because of the heterogeneous and potentially multifactorial origins of self-directed behaviours, the clinical evaluation should include a thorough general, dermatologic, and neurologic exam and appropriate laboratory testing (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…As discussed, outdoor access allows cats to demonstrate natural behaviors, and some have suggested that if these behaviors are prevented, it might lead to frustration, boredom, and the development of problematic behaviors, such as aggression, inappropriate urine marking or toileting, and furniture scratching [66]. Behavioral issues often indicate that welfare is negatively impacted, and the presence of these behavioral issues also puts cats at increased risk for other welfare issues like relinquishment or abandonment [67].…”
Section: Prevention Of Behavioral Problemsmentioning
confidence: 99%